Inducing An Axillary Bud of Dendrobium Red Emperor ‘Prince’ With An Addition of Bap in Vitro - Septasari, Mistri; Mercuriani, Ixora Sartika (Indonesian Journal of Bioscience (IJOBI), 2023)
The purpose of this study is to determine the effect of the addition of BAP and the position of nodus on the formation of axillary shoots and to know the optimum concentration of BAP for the induction of Dendrobium Red Emperor 'Prince' axial shoots. The research design used is a Complete Factorial Randomized Design consisting of one treatment, namely: concentration of growing regulatory substances (ZPT) BAP (0ppm, 1 ppm, 2 ppm, and 3 pmm), each treatment repeated 5 times. The explant of the nodus were taken from plants produced by previous in vitro culture having 5 nodi. The basic medium used is New Phalaenopsis (NP) + Coconut Water + 1 ppm 2.4-D). The growth of axillary bud growth is measured based on the time of the bud emergence, growth of crown, and that of root. Data obtained were then analyzed using ANOVA. If there was a significant difference, the analysis was continued with a test of DMRT with a significant level of 5%. The results showed the addition of concentrations of 1 ppm and 2 ppm BAP influenced the time of the bud emergence, growth of crown, and that of root. The optimum concentration of BAP to induce the orchid axillary shoots is 2 ppm.